Pulmonary Aplasia: A Case Report - Ali, Md Rustam; Mia, Md Sanaul Haque; Uddin, Md Belal; Rahman, Md Khalilur; Hossain, Md Belal; Tarofder, Md Manirul Haque (TAJ: Journal of Teachers Association, 2019)
Developmental malformations of the lung are common but aplasia of the lung is extremely rare and usually the patients presented in early childhood with recurrent lower respiratory tract infection and respiratory distress. A 2 years and 6 months old girl presented with complaints of respiratory distress since birth and recurrent episode of cough since six month of age ,with opacity of the right hemithorax on X-ray, CT scans shows aplasia of the right lung. Patient was managed conservatively and his parents were counseled about the anomaly. The child is doing well and is in a regular follow-up with us. Aplasia of the lung should be suspected in children with recurrent respiratory distress with opacity of the hemithorax on X-ray and herniation of the opposite lung across the mediastinum. TAJ 2019; 32(1): 82-85